Negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

By using a negative electrode material composed of specific graphite particles in lithium-ion secondary batteries, the problem of taking into account both input characteristics and high-temperature storage characteristics is solved, and the high performance of lithium-ion secondary batteries is achieved, which is suitable for high-performance applications such as electric vehicles.

CN113228351BActive Publication Date: 2024-12-27RESONAC CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201980087323.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-01-04
Publication Date
2024-12-27
Estimated Expiration
2039-01-04

AI Technical Summary

Technical Problem

The negative electrode material of existing lithium-ion secondary batteries is difficult to take into account both the input characteristics and the high-temperature storage characteristics. On the one hand, it will lead to performance degradation on the other hand.

Method used

Using a lithium-ion secondary battery negative electrode material containing specific graphite particles, the R value determined by Raman spectroscopy of graphite particles is less than 0.27, and the intensity ratio of the hexagonal crystal structure and the rhomboid structure in the X-ray diffraction pattern is less than or equal to 5.0, carbon (002) plane to carbon (110) plane intensity ratio is less than or equal to 1000, and the volume average particle size of graphite particles is between 2μm and 30μm, the BET specific surface area is between 2m2/g and 15m2/g, and the average circularity is between 85 or equal to 85. %, the average aspect ratio is less than or equal to 1.6, and amorphous carbon is present on the surface.

Benefits of technology

It realizes lithium-ion secondary batteries with excellent input characteristics and high-temperature storage characteristics, and is suitable for high-performance applications such as electric vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003140543700000201
    Figure BDA0003140543700000201
  • Figure BDA0003140543700000211
    Figure BDA0003140543700000211
Patent Text Reader

Abstract

A negative electrode material for a lithium-ion secondary battery comprises graphite particles, wherein the R value of the graphite particles measured by Raman spectroscopy is less than 0.27, and the intensity ratio (P1 / P2) of the diffraction peak (P1) of the hexagonal structure (101) plane to the diffraction peak (P2) of the rhombohedral structure (101) plane in an X-ray diffraction pattern obtained using CuKα rays is less than or equal to 5.0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a negative electrode material for a lithium ion secondary battery, a negative electrode for a lithium ion secondary battery and a lithium ion secondary battery. Background Art

[0002] Lithium-ion secondary batteries are small, lightweight, and have high energy density. They have been widely used in electronic devices such as notebook personal computers (PCs), mobile phones, smart phones, and tablet PCs. In recent years, against the backdrop of environmental issues such as global warming caused by CO2 emissions, clean electric vehicles (EVs) that use only batteries for driving, hybrid electric vehicles (HEVs) that combine gasoline engines and batteries, and plug-in hybrid electric vehicles (PHEVs) have become increasingly popular. As batteries installed in EVs, HEVs, PHEVs, etc., lithium-ion secondary batteries (on-board lithium-ion secondary batteries) are used. In addition, lithium-ion secondary batteries have recently been used for power storage, and the use of lithium-ion secondary batteries has been expanded in many fields.

[0003] The performance of the negative electrode material of a lithium-ion secondary battery has a great influence on the input characteristics of the lithium-ion secondary battery. Carbon materials are widely used as materials for negative electrode materials for lithium-ion secondary batteries. The carbon materials used in negative electrode materials are roughly divided into graphite and carbon materials (amorphous carbon, etc.) with lower crystallinity than graphite. Graphite has a structure composed of hexagonal mesh planes of carbon atoms stacked regularly. When it is made into a negative electrode material for a lithium-ion secondary battery, lithium ions are inserted and separated from the ends of the hexagonal mesh planes, thereby performing charging and discharging.

[0004] In amorphous carbon, the stacking of hexagonal mesh planes is irregular or does not have hexagonal mesh planes. In the negative electrode material using amorphous carbon, the insertion reaction and the separation reaction of lithium ions are carried out on the entire surface of the negative electrode material. Therefore, compared with the case where graphite is used as the negative electrode material, it is easy to obtain a lithium ion battery with excellent output characteristics (for example, refer to patent documents 1 and patent documents 2). On the other hand, amorphous carbon has a lower energy density than graphite because its crystallinity is lower than that of graphite.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 4-370662

[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 5-307956 Summary of the invention

[0009] Problems to be solved by the invention

[0010] For lithium-ion secondary batteries for vehicles such as EV, HEV, and PHEV, negative electrode materials that can further improve input characteristics related to regeneration efficiency, rapid charging, etc. are required. In addition, high-temperature storage characteristics are also required for lithium-ion secondary batteries for vehicles. However, it is difficult to take into account both input characteristics and high-temperature storage characteristics at a higher level. In general, if the specific surface area of ​​the negative electrode material is increased in order to improve the input characteristics, there is a tendency for the high-temperature storage characteristics to deteriorate. On the other hand, if the specific surface area of ​​the negative electrode material is reduced in order to improve the high-temperature storage characteristics, there is a tendency for the input characteristics to deteriorate. In this way, the input characteristics and high-temperature storage characteristics are generally in a relationship of one increasing while the other decreases.

[0011] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a negative electrode material for a lithium ion secondary battery, a negative electrode for a lithium ion secondary battery, and a lithium ion secondary battery having excellent input characteristics and high-temperature storage characteristics.

[0012] Methods for solving problems

[0013] The present invention includes the following aspects.

[0014] <1> A negative electrode material for a lithium ion secondary battery comprises graphite particles, wherein the graphite particles have an R value of less than 0.27 as measured by Raman spectroscopy, and an intensity ratio (P1 / P2) of a diffraction peak (P1) of a hexagonal structure (101) plane to a diffraction peak (P2) of a rhombohedral structure (101) plane in an X-ray diffraction pattern obtained using CuKα rays is less than or equal to 5.0.

[0015] <2> A negative electrode material for a lithium ion secondary battery, comprising graphite particles, wherein the graphite particles have an R value of less than 0.27 as determined by Raman spectroscopy, and an intensity ratio (P3 / P4) of a diffraction peak (P3) of a carbon (002) plane to a diffraction peak (P4) of a carbon (110) plane in an X-ray diffraction pattern obtained using CuKα rays is less than or equal to 1000.

[0016] <3> like <1> or <2> The negative electrode material for lithium-ion secondary batteries has a volume average particle size of graphite particles of 2 μm to 30 μm.

[0017] <4> like <1> ~ <3> The negative electrode material for lithium ion secondary battery according to any one of the preceding claims, wherein the BET specific surface area of ​​the graphite particles in a nitrogen adsorption method is 2 m 2 / g~15m 2 / g.

[0018] <5> like <1> ~ <4> In any one of the negative electrode materials for lithium ion secondary batteries, the average circularity of the graphite particles is greater than or equal to 85%.

[0019] <6> like <1> ~ <5> In any one of the negative electrode materials for lithium ion secondary batteries, the average aspect ratio (major axis / minor axis) of the graphite particles is less than or equal to 1.6.

[0020] <7> like <1> ~ <6> The negative electrode material for a lithium ion secondary battery described in any one of the above aspects has amorphous carbon on at least a portion of the surface of the graphite particles.

[0021] <8> A negative electrode for a lithium ion secondary battery, comprising: <1> ~ <7> A negative electrode material layer of the negative electrode material for a lithium ion secondary battery as described above, and a current collector.

[0022] <9> A lithium ion secondary battery comprising: <8> The lithium-ion secondary battery comprises a negative electrode, a positive electrode, and an electrolyte.

[0023] Effects of the Invention

[0024] According to the present invention, a negative electrode material for a lithium ion secondary battery, a negative electrode for a lithium ion secondary battery, and a lithium ion secondary battery excellent in input characteristics and high-temperature storage characteristics can be provided. DETAILED DESCRIPTION

[0025] Hereinafter, the mode for implementing the present invention is described in detail. However, the present invention is not limited to the following embodiments. In the following embodiments, its constituent elements (including element steps, etc.) are not necessary except for the cases specifically indicated. The same is true about numerical values ​​and their ranges, and the present invention is not limited thereto.

[0026] In the present disclosure, in a numerical range expressed using “to”, the numerical values ​​described before and after including “to” are respectively regarded as the minimum value and the maximum value.

[0027] In the numerical range recorded in stages in the present disclosure, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in the present disclosure, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiment.

[0028] In the present disclosure, each component may include multiple substances equivalent to each component. When multiple substances equivalent to each component exist in the negative electrode material or composition, unless otherwise specified, the content or content of each component refers to the total content or content of the multiple substances present in the negative electrode material or composition.

[0029] The present disclosure may include multiple types of particles corresponding to each component. When multiple types of particles corresponding to each component exist in the negative electrode material or composition, unless otherwise specified, the particle size of each component refers to the value for the mixture of the multiple types of particles present in the negative electrode material or composition.

[0030] In the present disclosure, the term "layer" includes not only a case where the layer is formed in the entire region when the region where the layer exists is observed, but also a case where the layer is formed in only a part of the region.

[0031] <Negative electrode materials for lithium-ion secondary batteries>

[0032] The negative electrode material for a lithium ion secondary battery disclosed herein comprises: an R value measured by Raman spectroscopy is less than 0.27, and an intensity ratio (P1 / P2) of a diffraction peak (P1) of a hexagonal structure (101) plane to a diffraction peak (P2) of a rhombohedral structure (101) plane in an X-ray diffraction pattern obtained using CuKα rays is less than or equal to 5.0.

[0033] In addition, the negative electrode material for a lithium ion secondary battery disclosed in the present invention comprises: graphite particles having an R value of less than 0.27 as measured by Raman spectroscopy and an intensity ratio (P3 / P4) of a diffraction peak (P3) of a carbon (002) plane to a diffraction peak (P4) of a carbon (110) plane in an X-ray diffraction pattern obtained using CuKα rays of less than or equal to 1000.

[0034] The negative electrode material for lithium ion secondary batteries may contain other components as necessary.

[0035] By using the negative electrode material for a lithium ion secondary battery of the present disclosure, a lithium ion secondary battery having excellent input characteristics and high-temperature storage characteristics can be obtained.

[0036] The negative electrode material for lithium ion secondary battery disclosed in the present invention comprises graphite particles. In the X-ray diffraction pattern of the graphite particles obtained by using CuKα rays, the intensity ratio (P1 / P2) of the diffraction peak (P1) of the hexagonal structure (101) plane to the diffraction peak (P2) of the rhombohedral structure (101) plane is less than or equal to 5.0, or in the X-ray diffraction pattern obtained by using CuKα rays, the intensity ratio (P3 / P4) of the diffraction peak (P3) of the carbon (002) plane to the diffraction peak (P4) of the carbon (110) plane is less than or equal to 1000.

[0037] Regarding the intensity ratio (P1 / P2), the smaller the value, the more the content of graphite particles with a rhombohedral structure. Graphite particles with a rhombohedral structure are generated, for example, by pressurizing naturally produced flaky graphite during mechanical spheroidization. Therefore, as a method for making the intensity ratio (P1 / P2) less than or equal to 5.0, a method of applying external pressure to graphite can be cited. Specifically, as a method for applying external pressure treatment, a method using a device such as a hybridization system (Hybridization System) (Nara Machinery Manufacturing Co., Ltd.) can be cited.

[0038] In addition, regarding the strength ratio (P3 / P4), the smaller its value is, the smaller the carbon network interlayer (002) is. Graphite particles with small carbon network interlayer (002) are generated, for example, by pressurizing naturally produced flaky graphite during mechanical spheroidization. It should be noted that the carbon network interlayer (002) of graphite, which is crystalline carbon, is smaller than that of amorphous carbon. Therefore, as a method for making the strength ratio (P3 / P4) less than or equal to 1000, a method of applying external pressure treatment to graphite can be cited. Specifically, as a method for applying external pressure treatment, a method using a device such as a hybrid system (Hybridization System) (Nara Machinery Manufacturing Co., Ltd.) can be cited.

[0039] The intensity ratio (P1 / P2) of the graphite particles may be 5.0 or less, preferably 4.5 or less, more preferably 4.0 or less, further preferably 3.7 or less, and particularly preferably 3.6 or less.

[0040] The intensity ratio (P3 / P4) of the graphite particles may be 1000 or less, preferably 500 or less, more preferably 300 or less, further preferably 200 or less, and particularly preferably 150 or less.

[0041] The X-ray diffraction pattern of graphite particles using CuKα rays can be obtained by irradiating a sample (graphite particles) with CuKα rays and measuring diffraction lines using a goniometer. Specifically, the measurement can be performed under the following conditions.

[0042] Monochromator: Crystal monochromator

[0043] Scan mode: 2θ / θ

[0044] Scan Type: Continuous

[0045] Output: 40kV, 30mA

[0046] Divergence slit: 5°

[0047] Scattering slit: 5°

[0048] Light receiving slit: 10mm

[0049] Measuring range: 0°≤2θ≤80°

[0050] Sampling amplitude: 0.01°

[0051] In the obtained X-ray diffraction pattern, the half-value width 2θ of the peak was calculated by conversion according to the following Bragg formula. The diffraction peaks having peak tops at the diffraction angles (2θ±0.2°) at the following positions are P1, P2, P3, and P4, respectively.

[0052] Bragg formula: 2dsinθ=nλ

[0053] Here, d represents the interplanar spacing, θ represents the diffraction angle, n represents the number of reflections, and λ represents the X-ray wavelength (0.15418 nm).

[0054] Diffraction peak P1: diffraction angle around 44°~45°

[0055] Diffraction peak P2: diffraction angle around 42.5°~43.5°

[0056] Diffraction peak P3: diffraction angle around 26°~27°

[0057] Diffraction peak P4: diffraction angle around 70°~80°

[0058] It should be noted that, regardless of whether it is the coated graphite particles described later or the graphite particles not coated with amorphous carbon, the suitable range of the intensity ratio (P1 / P2) is as described above. In addition, regardless of whether it is the coated graphite particles described later or the graphite particles not coated with amorphous carbon, the suitable range of the intensity ratio (P3 / P4) is as described above.

[0059] The R value of the graphite particles measured by Raman spectroscopy was less than 0.27.

[0060] The R value is: In Raman spectroscopy using a green laser with a wavelength of 532 nm, at a wave number of 1350 cm -1 ~1370cm -1 The peak intensity I of the second peak P2 with the maximum intensity is shown in the range of 1350 Relative to the wave number 1580cm -1 ~1620cm -1 The peak intensity I of the first peak P1 with the maximum intensity is shown in the range of 1580 The ratio (I 1350 / I 1580 Here, the wavelength of 1580 cm -1 ~1620cm -1 The first peak P1 that appears in the range of 1350 cm is usually identified as a peak corresponding to the graphite crystal structure. -1 ~1370cm -1 The second peak P2 appearing in the range of is generally identified as a peak corresponding to the amorphous structure of carbon.

[0061] In the present disclosure, Raman spectroscopy is measured by irradiating a sample plate on which graphite particles are flattened with a semiconductor laser using a laser Raman spectrophotometer (eg, model: NRS-1000, JASCO Corporation). The measurement conditions are as follows.

[0062] Semiconductor laser wavelength: 532nm

[0063] Wave number resolution: 2.56cm -1

[0064] Measuring range: 850cm -1 ~1950cm -1

[0065] Peak Finding: Removing Background

[0066] At least a portion of the surface of the graphite particles can be coated with amorphous carbon. By coating at least a portion of the surface of the graphite particles with amorphous carbon, the reactivity between the surface and the electrolyte is reduced, and there is a tendency to further improve the input-output characteristics while maintaining the initial charge and discharge efficiency well. Whether there is amorphous carbon on the surface of the graphite particles can be judged based on the results of observation using a transmission electron microscope (TEM). Hereinafter, the graphite particles obtained by coating at least a portion of the surface with amorphous carbon are also referred to as "coated graphite particles".

[0067] The content of amorphous carbon in the coated graphite particles is not particularly limited. From the viewpoint of improving input-output characteristics, the content of amorphous carbon is preferably greater than or equal to 0.1% by mass, more preferably greater than or equal to 0.5% by mass, and further preferably greater than or equal to 1% by mass, relative to the entire coated graphite particles. From the viewpoint of suppressing capacity decline, the content of amorphous carbon is preferably less than or equal to 30% by mass, more preferably less than or equal to 20% by mass, and further preferably less than or equal to 10% by mass.

[0068] The content of amorphous carbon can be determined by the following method.

[0069] (1) The coated graphite particles were heated at a temperature increase rate of 15°C / min, and the mass was measured in the range of 30°C to 950°C.

[0070] (2) The mass reduction at 30°C to 700°C is defined as the mass of amorphous carbon.

[0071] The content of amorphous carbon is calculated using the mass of the amorphous carbon by the following formula.

[0072] Amorphous carbon content (mass %) = (mass of amorphous carbon / mass of coated graphite particles at 30°C) × 100

[0073] The average thickness of amorphous carbon in the coated graphite particles is preferably 1 nm or more, more preferably 2 nm or more, and further preferably 3 nm or more, from the viewpoint of initial charge and discharge efficiency and input characteristics.

[0074] Furthermore, the average thickness of amorphous carbon in the coated graphite particles is preferably 500 nm or less, more preferably 300 nm or less, and further preferably 100 nm or less, from the viewpoint of energy density.

[0075] In the case of coated graphite particles, the R value is less than 0.27, preferably less than or equal to 0.26, and more preferably less than or equal to 0.25.

[0076] In the case of graphite particles whose surfaces are not coated with amorphous carbon, the R value is preferably 0.20 or less, more preferably 0.15 or less, and further preferably 0.14 or less.

[0077] The method for obtaining graphite particles having an intensity ratio (P1 / P2) or an intensity ratio (P3 / P4) within the above numerical range and an R value within the above range is not particularly limited, and for example, the following method can be cited: for spherical graphite particles having an intensity ratio (P1 / P2) or an intensity ratio (P3 / P4) within the above numerical range, heat treatment is performed in an atmosphere in the presence of CO2 gas, water vapor, O2 gas, etc. The reason why the R value can be within the above range by such heat treatment is unclear, but it can be inferred as follows.

[0078] For example, in the case of spheroidized graphite particles, the microparticles generated by the collapse during the mechanical spheroidization process will adhere to the surface of the spheroidized graphite particles. The crystallinity of the microparticles is low. It can be considered that by heat-treating the spheroidized graphite particles, the microparticles present on the surface will be burned and removed, so the R value is within the above range. However, the present invention is not limited to the above speculation. In addition, the graphite particles subjected to heat treatment are not limited to spheroidized graphite particles, as long as the intensity ratio (P1 / P2) or the intensity ratio (P3 / P4) is within the above numerical range. For example, it can also be artificial graphite.

[0079] The atmosphere of the heat treatment is preferably an atmosphere in which O2 gas is present (e.g., an air atmosphere). When the heat treatment is performed in an atmosphere in which O2 gas is present, the content of O2 gas is preferably 1% by volume to 30% by volume. By setting the content of O2 gas to within the above range, there is a tendency to effectively make the R value within the above range.

[0080] The heat treatment time is preferably appropriately set according to the gas atmosphere, treatment temperature, etc. For example, when heat treatment is performed in an air atmosphere, the heat treatment temperature is preferably 300° C. to 800° C., more preferably 400° C. to 750° C. Within this temperature range, there is a tendency that the R value can be within the above range.

[0081] The heat treatment time in air atmosphere varies depending on the heat treatment temperature, the type of graphite particles, etc., but is preferably 0.5 to 24 hours, more preferably 1 to 6 hours. Within this time, the R value tends to be effectively within the above range.

[0082] In addition, when the heat treatment atmosphere is set to a CO2 gas atmosphere, the heat treatment temperature is preferably 600° C. to 1000° C., and more preferably 700° C. to 900° C. In addition, although the heat treatment time under the CO2 gas atmosphere varies depending on the heat treatment temperature and the type of carbon material, it is preferably 0.5 hour to 24 hours, and more preferably 1 hour to 6 hours.

[0083] The coated graphite particles can be obtained by coating the graphite particles with amorphous carbon after the above-mentioned heat treatment. Even if the graphite particles are not subjected to the above-mentioned heat treatment but are coated with amorphous carbon and then subjected to heat treatment, or are subjected to heat treatment while being coated with amorphous carbon, there is a tendency that the low-crystalline particles attached to the surface of the graphite particles are not fully removed, and it is sometimes difficult to make the R value within the above-mentioned range.

[0084] The coated graphite particles can be obtained by further heat treating (second heat treatment) a mixture of graphite particles subjected to the above heat treatment and a precursor of amorphous carbon. The precursor of amorphous carbon is not particularly limited as long as it is a substance that can be changed into amorphous carbon by heat treatment, and asphalt, organic polymer compounds, etc. can be cited.

[0085] Examples of the asphalt include ethylene heavy end fraction asphalt, crude oil asphalt, coal tar pitch, asphalt decomposition asphalt, asphalt produced by thermal decomposition of polyvinyl chloride or the like, and asphalt produced by polymerizing naphthalene or the like in the presence of a super acid.

[0086] The softening point of the pitch is preferably 70 to 250° C., more preferably 75 to 150° C., and even more preferably 80 to 120° C. The softening point of the pitch is a value determined by the softening point measurement method (ring and ball method) of tar pitch described in JIS K 2425:2006.

[0087] Examples of the organic polymer compound include thermoplastic resins such as polyvinyl chloride, polyvinyl alcohol, polyvinyl acetate, and polyvinyl butyral, and natural substances such as starch and cellulose.

[0088] In the mixture, in addition to the precursor of amorphous carbon, other carbonaceous materials (carbonaceous particles, etc.) in particulate form may be included as needed. When the mixture includes a precursor of amorphous carbon and carbonaceous particles, the material of the amorphous carbon formed by the precursor of amorphous carbon and the carbonaceous particles may be the same or different.

[0089] The carbonaceous particles used as other carbonaceous materials are not particularly limited, and examples thereof include particles of acetylene black, oil furnace black, Ketjen black, channel black, thermal black, and earthy graphite.

[0090] The method for preparing the mixture is not particularly limited, and examples thereof include wet mixing, powder mixing, and mechanical mixing.

[0091] In wet mixing, graphite particles subjected to heat treatment, a precursor of amorphous carbon, and other carbonaceous materials (carbonaceous particles, etc.) as needed are mixed in a solvent, and then the solvent is removed.

[0092] In powder mixing, graphite particles and amorphous carbon precursor, and other carbonaceous materials (carbonaceous particles, etc.) as needed are mixed in a powder state.

[0093] In the mechanical mixing, graphite particles, amorphous carbon precursor, and other carbonaceous materials (carbonaceous particles, etc.) as needed are mixed while applying mechanical energy.

[0094] The temperature at which the mixture is heat treated (second heat treatment) is not particularly limited. For example, it is preferably 700°C to 1500°C, more preferably 750°C to 1300°C, and further preferably 800°C to 1100°C. From the viewpoint of fully carbonizing the precursor of the amorphous carbon, the temperature of the second heat treatment is preferably greater than or equal to 700°C. The temperature of the second heat treatment may be fixed from the beginning to the end of the second heat treatment, or may vary.

[0095] The time of the second heat treatment is appropriately adjusted according to the type of amorphous carbon precursor. For example, when using coal tar pitch with a softening point of 100°C (±20°C) as a precursor of amorphous carbon, it is preferably heated to 400°C at a rate of less than or equal to 10°C / minute. In addition, the total time of the heating process included in the second heat treatment is preferably 2 hours to 18 hours, more preferably 3 hours to 15 hours, and further preferably 4 hours to 12 hours.

[0096] The atmosphere of the second heat treatment is not particularly limited as long as it is an inert gas atmosphere such as nitrogen or argon, but a nitrogen atmosphere is preferred from an industrial viewpoint.

[0097] The burned product obtained by the second heat treatment may be pulverized by a cutter, a feather mill, a juicer mixer, etc. Alternatively, the pulverized burned product may be sieved.

[0098] The volume average particle size (D 50) is preferably 2 μm to 30 μm, more preferably 5 μm to 25 μm, and further preferably 7 μm to 20 μm. If the volume average particle size of the graphite particles is less than or equal to 30 μm, the discharge capacity and discharge characteristics tend to be improved. If the volume average particle size of the graphite particles is greater than or equal to 2 μm, the initial charge and discharge efficiency tends to be improved.

[0099] The volume average particle size (D 50 ), using a laser diffraction particle size distribution measuring device (e.g., SALD-3000J, Shimadzu Corporation), the volume-based particle size distribution is measured as D 50 (median diameter) and find it.

[0100] The BET specific surface area of ​​the graphite particles (in the case of graphite particles obtained by coating at least a part of the surface with amorphous carbon, coated graphite particles) in a nitrogen adsorption method is preferably 2 m 2 / g~15m 2 / g, more preferably 2m 2 / g~13m 2 / g.

[0101] If the BET specific surface area of ​​graphite particles is greater than or equal to 2 m 2 / g, the input characteristics tend to be further improved. In addition, if the BET specific surface area of ​​the graphite particles is less than or equal to 15m 2 / g, the tap density tends to be increased, and the miscibility with other materials such as a binder and a conductive material tends to be improved.

[0102] Furthermore, the BET specific surface area of ​​the uncoated graphite particles is more preferably 3 m 2 / g~15m 2 / g, particularly preferably 4m 2 / g~13m 2 / g.

[0103] Furthermore, the BET specific surface area of ​​the coated graphite particles is more preferably 2 m 2 / g~10m 2 / g, particularly preferably 2m 2 / g~8m 2 / g.

[0104] The BET specific surface area can be calculated by measuring nitrogen adsorption at liquid nitrogen temperature (77 K) using a one-point method according to JIS Z 8830: 2013. For example, FlowSorb III 2310 manufactured by Shimadzu Corporation can be used as a measuring apparatus, and nitrogen adsorption at liquid nitrogen temperature (77 K) can be measured using a mixed gas of nitrogen and helium (nitrogen:helium = 3:7) using a one-point method at a relative pressure of 0.3, and calculated by the BET method.

[0105] When measuring the BET specific surface area, it is considered that moisture adsorbed on the surface and structure of the sample affects the gas adsorption energy, so it is preferred to first perform a pretreatment to remove moisture by heating.

[0106] In the pretreatment, the sample cell for measurement, into which 0.05 g of the measurement sample is put, is depressurized to 10 Pa or less by a vacuum pump, and then heated at 110° C. and maintained for 3 hours or more, and then naturally cooled to room temperature (25° C.) while maintaining the depressurized state. After the pretreatment, the evaluation temperature can be set to 77 K, and the evaluation pressure range can be set to be less than 1 in relative pressure (equilibrium pressure relative to saturated vapor pressure) for measurement.

[0107] The average circularity of the graphite particles (in the case of graphite particles obtained by coating at least a portion of the surface with amorphous carbon, coated graphite particles) is preferably greater than or equal to 85%, more preferably greater than or equal to 88%, and further preferably greater than or equal to 89%.

[0108] The circularity of the graphite particles is a value obtained by dividing the circumference of a circle calculated from the diameter of a circle having the same area as the projected area of ​​the graphite particles, i.e., the equivalent circle diameter, by the circumference (contour length) measured from the projected image of the inorganic filler and multiplying by 100. It should be noted that the circularity is 100% when the shape is a perfect circle.

[0109] Circularity = {(circumference of equivalent circle) / (circumference of particle cross-section image)}×100

[0110] Specifically, the average circularity of graphite particles can be measured using a wet flow particle size and shape analyzer (e.g., Malvern, FPIA-3000). It should be noted that the measurement temperature is set to 25° C., the concentration of the measurement sample is set to 10% by mass, and the number of particles counted is set to 12,000. In addition, water is used as a solvent for dispersion.

[0111] When measuring the circularity of graphite particles, it is preferred to disperse the graphite particles in water in advance. For example, ultrasonic dispersion, vortex mixer, etc. can be used to disperse the graphite particles in water. In order to suppress the influence of particle collapse or particle destruction of graphite particles, the intensity and time of the ultrasonic wave can be appropriately adjusted in view of the intensity of the measured graphite particles.

[0112] As ultrasonic treatment, for example, after preferably storing any amount of water in the tank of ultrasonic cleaning device (ASU-10D, ASUWANG Co., Ltd.), the test tube of the dispersion liquid of graphite particles is immersed in the water in the tank together with the support, and ultrasonic treatment is carried out for 1 minute to 10 minutes. If within this processing time, it is easy to disperse the graphite particles under the state of particle collapse, particle destruction, sample temperature rise, etc. of the graphite particles suppressed.

[0113] The average aspect ratio (major axis / minor axis) of the graphite particles (in the case of graphite particles obtained by coating at least a portion of the surface with amorphous carbon, coated graphite particles) is preferably less than or equal to 1.6, more preferably less than or equal to 1.5, and further preferably less than or equal to 1.4.

[0114] When the average aspect ratio is 1.6 or less, the electrical conductivity of the electrode layer in the thickness direction tends to be further improved.

[0115] The average aspect ratio of graphite particles is obtained by magnifying the graphite particles with a microscope, randomly selecting 100 graphite particles, measuring the major axis / minor axis, and taking the arithmetic mean of the measured values. Here, the length in the major axis direction is the distance between A and A' when the interval between the two parallel lines A and A' is the largest when the graphite particles under observation are sandwiched in a contacting manner; the length in the minor axis direction is the distance between B and B' when the interval between the two parallel lines A and A' that determine the length in the major axis direction is the largest when the graphite particles are sandwiched in a contacting manner by two parallel lines B and B' that are perpendicular to the two parallel lines A and A' that determine the length in the major axis direction.

[0116] <Negative electrode for lithium ion secondary battery>

[0117] The negative electrode for lithium ion secondary battery disclosed in the present invention comprises: a negative electrode material layer containing the negative electrode material for lithium ion secondary battery disclosed in the present invention, and a current collector. In addition to the negative electrode material layer containing the negative electrode material for lithium ion secondary battery disclosed in the present invention and the current collector, the negative electrode for lithium ion secondary battery may also include other components as needed.

[0118] The negative electrode for lithium ion secondary battery can be made, for example, by mixing the negative electrode material for lithium ion secondary battery and the binder with a solvent to prepare a slurry-like negative electrode material composition for lithium ion secondary battery, and applying it on the collector to form a negative electrode material layer; or forming the negative electrode material composition for lithium ion secondary battery into a sheet, granular or other shape, and integrating it with the collector to make it. Mixing can be carried out using a dispersing device such as a mixer, a ball mill, a super sand mill, a pressure kneading machine, etc.

[0119] The binder used in the modulation of the negative electrode material composition for lithium ion secondary batteries is not particularly limited. As a binder, ethylene unsaturated carboxylic acid esters such as styrene-butadiene copolymer (SBR), methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, and acrylic acid, methacrylic acid, itaconic acid, fumaric acid, maleic acid, etc., and homopolymers or copolymers of ethylene unsaturated carboxylic acids such as maleic acid; polyvinylidene fluoride, polyethylene oxide, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polymethacrylonitrile, etc., which have large ion conductivity. In the case where the negative electrode material composition for lithium ion secondary batteries contains a binder, the content of the binder is not particularly limited. For example, it can be 0.5 to 20 parts by mass relative to a total of 100 parts by mass of the negative electrode material for lithium ion secondary batteries and the binder.

[0120] The negative electrode material composition for lithium ion secondary batteries may also include a thickener. As a thickener, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, polyacrylic acid or its salt, oxidized starch, phosphorylated starch, casein, etc. can be used. In the case where the negative electrode material composition for lithium ion secondary batteries includes a thickener, the content of the thickener is not particularly limited. For example, relative to 100 parts by mass of the negative electrode material for lithium ion secondary batteries, it can be 0.1 parts by mass to 5 parts by mass.

[0121] The negative electrode material composition for lithium ion secondary batteries may also contain a conductive auxiliary material. As conductive auxiliary materials, there can be listed: carbon materials such as carbon black, graphite, acetylene black; oxides showing conductivity; inorganic compounds such as nitrides showing conductivity, etc. In the case where the negative electrode material composition for lithium ion secondary batteries contains a conductive auxiliary material, the content of the conductive auxiliary material is not particularly limited. For example, relative to 100 parts by mass of the negative electrode material for lithium ion secondary batteries, it can be 0.5 parts by mass to 15 parts by mass.

[0122] The material of the current collector is not particularly limited, and can be selected from aluminum, copper, nickel, titanium, stainless steel, etc. The state of the current collector is not particularly limited, and can be selected from foil, perforated foil, mesh, etc. In addition, porous materials such as porous metal (foamed metal), carbon paper, etc. can also be used as the current collector.

[0123] When the negative electrode material composition for lithium ion secondary battery is applied to the collector to form a negative electrode material layer, the method is not particularly limited, and the known methods such as metal mask printing, electrostatic coating, dip coating, spraying, roller coating, scraper, notch wheel coating, gravure coating, screen printing, etc. can be used. After the negative electrode material composition for lithium ion secondary battery is applied to the collector, the solvent contained in the negative electrode material composition for lithium ion secondary battery is removed by drying. Drying can be carried out using, for example, a hot air dryer, an infrared dryer, or a combination of these devices. The negative electrode material layer can also be calendered as needed. The calendering process can be carried out using methods such as a flat press and a calender roll.

[0124] When the negative electrode material composition for lithium ion secondary batteries formed into a sheet, particle, etc. is integrated with the collector to form a negative electrode material layer, the method of integration is not particularly limited. For example, it can be carried out by a roller, a flat press, or a combination of these means. The pressure when the negative electrode material composition for lithium ion secondary batteries is integrated with the collector is preferably, for example, 1MPa to 200MPa.

[0125] The negative electrode density of the negative electrode material layer is not particularly limited. For example, it is preferably 1.1 g / cm 3 ~1.8g / cm 3 , more preferably 1.1 g / cm 3 ~1.7g / cm 3 , more preferably 1.1 g / cm 3 ~1.6g / cm 3 By setting the negative electrode density to be greater than or equal to 1.1 g / cm 3 , there is a tendency that the increase in resistance is suppressed and the capacity is increased, and by setting it to less than or equal to 1.8 g / cm 3 , there is a tendency that the decrease in input-output characteristics and cycle characteristics is suppressed.

[0126] <Lithium-ion secondary battery>

[0127] The lithium ion secondary battery of the present disclosure includes a negative electrode for a lithium ion secondary battery, a positive electrode, and an electrolyte solution.

[0128] The positive electrode can be obtained by forming a positive electrode material layer on a current collector in the same manner as the above-mentioned method for making the negative electrode. As the current collector, a current collector made of a metal or alloy such as aluminum, titanium, stainless steel, etc. in a foil, perforated foil, mesh, etc. can be used.

[0129] There is no particular limitation on the positive electrode material used to form the positive electrode layer. Examples of positive electrode materials include metal compounds (metal oxides, metal sulfides, etc.) that can be doped or embedded with lithium ions, conductive polymer materials, etc. More specifically, examples include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and their composite oxides (LiCo x Ni y Mn z O2, x+y+z=1), a composite oxide containing an additional element M' (LiCo a Ni b Mn c M' d O2, a+b+c+d=1, M': Al, Mg, Ti, Zr or Ge), spinel lithium manganese oxide (LiMn2O4), lithium vanadium compounds, V2O5, V6O 13 , VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, metal compounds such as olivine-type LiMPO4 (M: Co, Ni, Mn, Fe), conductive polymers such as polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene, porous carbon, etc. The positive electrode material can be a single type or two or more types.

[0130] The electrolyte solution is not particularly limited, and for example, an electrolyte solution (so-called organic electrolyte solution) obtained by dissolving a lithium salt as an electrolyte in a non-aqueous solvent can be used.

[0131] Examples of the lithium salt include LiCLO4, LiPF6, LiAsF6, LiBF4, LiSO3CF3, etc. The lithium salt may be a single type or two or more types.

[0132] Examples of the non-aqueous solvent include ethylene carbonate, fluoroethylene carbonate, chloroethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, cyclopentanone, cyclohexylbenzene, sulfolane, propane sultone, 3-methylsulfolane, 2,4-dimethylsulfolane, 3-methyl-1,3- Oxazolidin-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, methyl butyl carbonate, ethyl propyl carbonate, ethyl butyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, ethyl acetate, trimethyl phosphate, triethyl phosphate, etc. The non-aqueous solvent may be a single type or two or more types.

[0133] The state of the positive electrode and the negative electrode in the lithium ion secondary battery is not particularly limited. For example, the positive electrode and the negative electrode and the separator disposed between the positive electrode and the negative electrode as required may be wound in a spiral shape, or they may be formed into a flat plate shape and stacked.

[0134] The separator is not particularly limited, and for example, a nonwoven fabric, a cloth, a microporous membrane or a combination thereof made of a resin can be used. As the resin, a resin having a polyolefin such as polyethylene or polypropylene as a main component can be cited. In the structure of a lithium-ion secondary battery, when the positive electrode and the negative electrode are not in direct contact, a separator may not be used.

[0135] The shape of the lithium ion secondary battery is not particularly limited, and examples thereof include laminated batteries, paper batteries, button batteries, coin batteries, stacked batteries, cylindrical batteries, and square batteries.

[0136] The lithium ion secondary battery disclosed in the present invention is suitable as a large-capacity lithium ion secondary battery used in electric vehicles, power tools, power storage devices, etc. due to its excellent input characteristics and high-temperature storage characteristics. In particular, it is suitable as a lithium ion secondary battery used in electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc., which require charging and discharging at a large current in order to improve acceleration performance and brake regeneration performance.

[0137] Example

[0138] Hereinafter, the present invention will be described in further detail with reference to Examples, but the present invention is not limited to the following Examples.

[0139] <Example 1>

[0140] (1) Preparation of negative electrode material

[0141] 60 g of spherical natural graphite (volume average particle size: 10 μm) as graphite particles was placed in an alumina crucible with a capacity of 0.864 L and allowed to stand for 1 hour in an air atmosphere while being maintained at 500° C. to obtain a negative electrode material.

[0142] [Determination of R value]

[0143] Raman spectrometry was performed by irradiating a sample plate on which a negative electrode material was flattened with a semiconductor laser using a Raman spectrometer "Laser Raman Spectrophotometer (Model: NRS-1000, JASCO Corporation)" The measurement conditions were as follows.

[0144] Semiconductor laser wavelength: 532nm

[0145] Wave number resolution: 2.56cm -1

[0146] Measuring range: 850cm -1 ~1950cm -1

[0147] Peak Finding: Removing Background

[0148] [X-ray diffraction measurement]

[0149] The negative electrode material was filled in the concave part of the quartz sample holder and placed on the measurement platform. The measurement was performed using an X-ray diffraction device under the following measurement conditions. The details of the X-ray diffraction measurement using CuKα rays are as follows.

[0150] -Measurement apparatus and conditions-

[0151] X-ray diffraction instrument: ULtima IV, Rigaku Corporation

[0152] Monochromator: Crystal monochromator

[0153] Scan mode: 2θ / θ

[0154] Scan Type: Continuous

[0155] Output: 40kV, 30mA

[0156] Divergence slit: 5°

[0157] Scattering slit: 5°

[0158] Light receiving slit: 10mm

[0159] Measuring range: 0°≤2θ≤80°

[0160] Sampling amplitude: 0.01°

[0161] Based on the obtained X-ray diffraction pattern, the intensity ratio (P1 / P2) of the diffraction peak of the hexagonal structure (101) plane (P1: diffraction angle 2θ=44.3°) and the diffraction peak of the rhombohedral structure (101) plane (P2: diffraction angle 2θ=43.2°) was calculated.

[0162] In addition, based on the obtained X-ray diffraction pattern, the intensity ratio (P3 / P4) of the carbon (002) plane diffraction peak (P3) detected near the diffraction angle 2θ = 26°~27° and the carbon (110) plane diffraction peak (P4) detected near the diffraction angle 2θ = 70°~80° was calculated.

[0163] [Volume average particle size]

[0164] The negative electrode material and the surfactant are dispersed in purified water to obtain a dispersion, and the obtained dispersion is placed in the sample water tank of a laser diffraction particle size distribution measuring device (SALD-3000J, Shimadzu Corporation). Then, while applying ultrasonic waves to the dispersion, a pump is used to circulate it, and the volume cumulative 50% particle size of the obtained particle size distribution is obtained as the volume average particle size.

[0165] [Measurement of specific surface area]

[0166] Regarding the specific surface area of ​​the negative electrode material, a specific surface area / pore distribution measuring device (FlowSorb III2310, Shimadzu Corporation) was used. A mixed gas of nitrogen and helium (nitrogen:helium = 3:7) was used to measure nitrogen adsorption at liquid nitrogen temperature (77K) using a one-point method at a relative pressure of 0.3, and the result was calculated by the BET method.

[0167] [Measurement of average circularity]

[0168] The negative electrode material was placed in water to prepare a 10% by mass aqueous dispersion to obtain a test sample. The test tube containing the test sample and the stand were placed in water stored in a tank of an ultrasonic cleaner (ASU-10D, ASUON Co., Ltd.). Then, an ultrasonic treatment was performed for 1 to 10 minutes.

[0169] After the ultrasonic treatment, the average circularity of the graphite particles was measured at 25° C. using a wet flow type particle size and shape analyzer (Malvern, FPIA-3000). The number of particles counted was set to 12,000.

[0170] [Determination of average aspect ratio]

[0171] Regarding the graphite particles, the graphite particles were magnified with an electron microscope, 100 graphite particles were randomly selected, the major axis / minor axis ratio was measured by the above method, and the arithmetic mean value was calculated.

[0172] (2) Fabrication of lithium-ion secondary batteries

[0173] For 98 parts by mass of the negative electrode material, an aqueous solution of CMC (carboxymethyl cellulose, Daiichi Kogyo Seiyaku Co., Ltd., Cellogen WS-C) as a thickener was added in such a manner that the solid content of CMC became 1 part by mass (CMC concentration: 2% by mass), and kneading was performed for 10 minutes. Next, purified water was added several times in such a manner that the total solid content concentration of the negative electrode material and CMC became 45% to 60% by mass, and kneading was performed for 10 minutes. Next, an aqueous dispersion of SBR (styrene-butadiene copolymer, BM400-B, ZEON Co., Ltd., Japan) as a binder was added in such a manner that the solid content of SBR became 1 part by mass (SBR concentration: 40% by mass), and mixed for 10 minutes to prepare a paste-like negative electrode material composition for lithium-ion secondary batteries (negative electrode material composition). Next, using a notched wheel coater with the gap adjusted, the negative electrode material composition was coated in an amount of 4.5 mg / cm per unit area. 2 The negative electrode material layer was formed by coating the negative electrode material on an electrolytic copper foil with a thickness of 11 μm. Then, the negative electrode density was adjusted to 1.2 g / cm using a hand press. 3 The electrolytic copper foil on which the negative electrode material layer was formed was punched into a disk shape with a diameter of 14 mm to prepare a sample electrode (negative electrode).

[0174] As the positive electrode active material, (LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2)(BET specific surface area: 0.4m 2 / g, average particle size (D50): 6.5μm). For the positive electrode active material, acetylene black (trade name: HS-100, average particle size 48nm (DENKA Co., Ltd. catalog value), manufactured by DENKA Co., Ltd.) as a conductive material and polyvinylidene fluoride as a binder are added in sequence and mixed to obtain a mixture of positive electrode materials. The mass ratio is set to positive electrode active material: conductive material: binder = 80:13:7. Furthermore, N-methyl-2-pyrrolidone (NMP) is added to the above mixture as a dispersing solvent, and kneading is performed to form a slurry. The slurry is substantially evenly and homogeneously applied to both sides of an aluminum foil with an average thickness of 20μm as a positive electrode collector. Thereafter, a drying treatment is carried out, and compaction is performed using a press until the density is 2.7g / cm 3 Until now, the positive electrode is made.

[0175] The sample electrode (negative electrode), separator, and positive electrode are placed in a coin-shaped battery container in this order, and an electrolyte is injected to make a coin-shaped lithium-ion secondary battery. As the electrolyte, an electrolyte prepared by dissolving LiPF6 in a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (the volume ratio of EC to EMC is 3:7) at a concentration of 1.0 mol / L is used. The initial negative electrode capacity / initial positive electrode capacity is designed to be 1.2.

[0176] As a separator, a polyethylene microporous membrane with a thickness of 20 μm was used. The prepared lithium ion secondary battery was CC charged to 4.2V at a current value equivalent to 0.2CA, and then CV charged to a level equivalent to 0.02CA. After that, it was rested for 30 minutes, discharged to 2.7V at a current value equivalent to 0.2CA, and rested for 30 minutes. This series of steps was regarded as 1 cycle, and it was repeated for 3 cycles to initialize. Using the initialized lithium ion secondary battery, the input characteristics and high temperature storage characteristics were evaluated by the following method.

[0177] [Evaluation of input characteristics]

[0178] The input characteristics are evaluated by direct current resistance (DCR).

[0179] (1) The initialized lithium ion secondary battery is charged at a current value equivalent to 0.2 CA until the SOC is 50%.

[0180] (2) Charge for 11 seconds at a current equivalent to 0.1 CA and find the voltage change at the 10th second.

[0181] (3) Next, the SOC is adjusted to 50% again, and then the battery is charged for 11 seconds at a current value corresponding to 0.2 CA, and the voltage change at the 10th second is calculated.

[0182] (4) Perform the same operation to find the voltage change at 0.5CA, plot each current value and the corresponding voltage change, and set the slope as DCR (Ω). The slope is calculated by the least squares method. All measurements are carried out in a constant temperature chamber at 25°C, and the interval between each measurement is set to 15 minutes.

[0183] [Evaluation of high temperature storage characteristics]

[0184] (1) The initialized lithium ion secondary battery is charged to 4.2 V at a current value equivalent to 0.2 CA, and then charged at a constant voltage of 4.2 V until the current value reaches a level equivalent to 0.02 CA. Then, the battery is discharged at a constant current value equivalent to 0.2 CA to 2.7 V. The discharge capacity at this time is defined as "discharge capacity 1" (mAh).

[0185] (2) The battery was charged at a constant current of 0.2 CA to 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached a level equivalent to 0.02 CA. The measurements up to this point were performed in a thermostatic chamber at 25° C., with each measurement interval set to 15 minutes.

[0186] (3) The battery of (2) was left to stand in a constant temperature chamber at 60°C for 14 days.

[0187] (4) The battery of (3) was left to stand in a thermostatic chamber at 25°C for 5 hours, and then discharged at a constant current of 0.2 CA to 2.7 V. After a 15-minute interval, the battery was discharged at a constant current of 0.2 CA to 2.7 V.

[0188] (5) The battery of (4) was charged to 4.2 V at a constant current of 0.2 CA in a thermostatic chamber at 25°C, and then charged at a constant voltage of 4.2 V until the current value reached a level equivalent to 0.02 CA. Next, the battery was discharged to 2.7 V at a constant current of 0.2 CA. The discharge capacity at this time was defined as "discharge capacity 2" (mAh). The measurement interval was set to 15 minutes.

[0189] (6) From the “discharge capacity 1” obtained in (1) and the “discharge capacity 2” obtained in (5), the high-temperature storage characteristics were obtained using the following (Formula 1).

[0190] High temperature storage characteristics (%) = (discharge capacity 2 / discharge capacity 1) × 100

[0191] <Example 2>

[0192] In the same manner as in Example 1, except that the heat treatment temperature of the graphite particles was set to 600° C., a negative electrode material and a lithium ion secondary battery were produced and evaluated.

[0193] <Example 3>

[0194] In the same manner as in Example 1, except that the heat treatment temperature of the graphite particles was set to 700° C., a negative electrode material and a lithium ion secondary battery were produced and evaluated.

[0195] <Comparative Example 1>

[0196] The graphite particles used as the raw material of Example 1 were not subjected to heat treatment but were used as a negative electrode material to produce a lithium ion secondary battery, which was evaluated in the same manner as in Example 1. Table 1 shows the obtained results.

[0197] <Comparative Example 2>

[0198] The flaky graphite particles were used as a negative electrode material without heat treatment to produce a lithium ion secondary battery, and the battery was evaluated in the same manner as in Example 1. Table 1 shows the results obtained.

[0199] <Example 4>

[0200] 100 parts by mass of the negative electrode material obtained in Example 1 is powdered and mixed with 7.5 parts by mass of coal tar pitch (softening point: 98°C, residual carbon rate: 50% by mass) to obtain a mixture. Next, the mixture is heat-treated to prepare a sintered product having amorphous carbon attached to the surface of the negative electrode material obtained in Example 1. The heat treatment is carried out by heating from 25°C to 1000°C at a heating rate of 200°C / hour under nitrogen flow, and maintaining at 1000°C for 1 hour. The sintered product having amorphous carbon attached to the surface of the negative electrode material obtained in Example 1 is crushed using a shredder, sieved using a 350-mesh sieve, and the sieved material is used as a negative electrode material (negative electrode material) for lithium-ion secondary batteries. A lithium-ion secondary battery is made using the obtained negative electrode material, and the evaluation is carried out in the same manner as in Example 1. The results obtained are shown in Table 2.

[0201] <Example 5>

[0202] The same operation as in Example 4 was performed, but the negative electrode material obtained in Example 2 was used to obtain a negative electrode material for a lithium ion secondary battery having amorphous carbon attached to the surface (negative electrode material). A lithium ion secondary battery was prepared using the obtained negative electrode material, and the evaluation was performed in the same manner as in Example 1. The obtained results are shown in Table 2.

[0203] <Example 6>

[0204] The same operation as in Example 4 was performed, but the negative electrode material obtained in Example 3 was used to obtain a negative electrode material for a lithium ion secondary battery having amorphous carbon attached to the surface (negative electrode material). A lithium ion secondary battery was prepared using the obtained negative electrode material, and the evaluation was performed in the same manner as in Example 1. The obtained results are shown in Table 2.

[0205] <Comparative Example 3>

[0206] The same operation as in Example 4 was performed, but the graphite particles used as the raw material of Example 1 were not subjected to heat treatment and were directly used as the negative electrode material, thereby obtaining a negative electrode material for a lithium ion secondary battery (negative electrode material) having amorphous carbon attached to the surface. A lithium ion secondary battery was prepared using the obtained negative electrode material, and the evaluation was performed in the same manner as in Example 1. The obtained results are shown in Table 2.

[0207] <Comparative Example 4>

[0208] The same operation as in Example 4 was performed, but the flaky graphite particles were not heat treated and were directly used as negative electrode materials, thereby obtaining a negative electrode material for a lithium ion secondary battery (negative electrode material) having amorphous carbon attached to the surface. A lithium ion secondary battery was prepared using the obtained negative electrode material, and the evaluation was performed in the same manner as in Example 1. The obtained results are shown in Table 2.

[0209] [Table 1]

[0210]

[0211] [Table 2]

[0212]

[0213] As shown in the results of Tables 1 and 2, it is found that the lithium ion secondary battery produced using the negative electrode material of the example has superior input characteristics and high temperature storage characteristics compared to the lithium ion secondary battery produced using the negative electrode material of the comparative example.

Claims

1. A negative electrode material for a lithium ion secondary battery, comprising graphite particles, wherein the graphite particles are coated graphite particles or graphite particles not coated with amorphous carbon, wherein the R value of the graphite particles measured by Raman spectroscopy is less than 0.27, and in an X-ray diffraction pattern obtained using CuKα rays, the intensity ratio P1 / P2 of the diffraction peak P1 of the hexagonal structure (101) plane to the diffraction peak P2 of the rhombohedral structure (101) plane is less than or equal to 5.0, and in an X-ray diffraction pattern obtained using CuKα rays, the intensity ratio P3 / P4 of the diffraction peak P3 of the carbon (002) plane to the diffraction peak P4 of the carbon (110) plane is less than 84, and the average aspect ratio of the graphite particles, i.e., the major axis / minor axis, is less than or equal to 1.

19. 2 . The negative electrode material for a lithium ion secondary battery according to claim 1 , wherein the volume average particle size of the graphite particles is 2 μm to 30 μm.

3. The negative electrode material for lithium ion secondary battery according to claim 1 or 2, wherein the BET specific surface area of ​​the graphite particles in a nitrogen adsorption method is 2 m 2 / g~15m 2 / g. 4 . The negative electrode material for a lithium ion secondary battery according to claim 1 , wherein the average circularity of the graphite particles is greater than or equal to 85%. 5 . The negative electrode material for a lithium ion secondary battery according to claim 1 , wherein at least a portion of the surface of the graphite particles has amorphous carbon. 6 . A negative electrode for a lithium ion secondary battery, comprising: a negative electrode material layer containing the negative electrode material for a lithium ion secondary battery according to claim 1 , and a current collector. 7 . A lithium ion secondary battery comprising: the negative electrode for the lithium ion secondary battery according to claim 6 , a positive electrode, and an electrolyte.

Citation Information

Patent Citations

  • Electrode for secondary battery

    JP1992370662A

  • Nonaqueous group secondary battery

    JP1993307956A

  • Nonaqueous electrolyte secondary cell and method for manufacturing same

    CN103620836A

  • Negative electrode material for lithium-ion secondary cell, method for manufacturing negative electrode material for lithium-ion secondary cell, negative electrode material slurry for lithium-ion secondary cell, negative electrode for lithium-ion secondary cell, and lithium-ion secondary cell

    CN106104871A

  • Nonaqueous Electrolyte Battery And Battery Pack

    CN108281658A